2020
DOI: 10.7717/peerj.10231
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sediment DNA extraction methods for assessing organic enrichment associated with marine aquaculture

Abstract: Marine sediments contain a high diversity of micro- and macro-organisms which are important in the functioning of biogeochemical cycles. Traditionally, anthropogenic perturbation has been investigated by identifying macro-organism responses along gradients. Environmental DNA (eDNA) analyses have recently been advocated as a rapid and cost-effective approach to measuring ecological impacts and efforts are underway to incorporate eDNA tools into monitoring. Before these methods can replace or complement existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 78 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…DNA extractions were performed using the PowerSoil DNA extraction kit (Qiagen) according to manufacturer instructions with the addition of 15 μg ml −1 lysozyme. The PowerSoil DNA extraction kit was used because of established higher prokaryotic diversity yields in previous studies (34). All DNA isolates were stored at −20°C until sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extractions were performed using the PowerSoil DNA extraction kit (Qiagen) according to manufacturer instructions with the addition of 15 μg ml −1 lysozyme. The PowerSoil DNA extraction kit was used because of established higher prokaryotic diversity yields in previous studies (34). All DNA isolates were stored at −20°C until sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…While both of these commercial kits are routinely used to extract high-quality nucleic acids from environmental samples, subtle differences in the physicochemical properties of sediments and the corresponding kit chemistry may impact the recovery of genetic material, hence leading to significant differences in microbial community composition (Zielińska et al, 2017). Further research is required to better comprehend the implications of kit selection (Pearman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Before molecular techniques can be robustly applied to the analysis of biological communities in sediment cores, there are a number of methodological considerations that need to be addressed. For example, numerous studies using metabarcoding approaches have shown that DNA extraction efficiency and taxonomic coverage of microbial species in sediments is substantially different depending on the DNA extraction method applied [14][15][16][17]. A comprehensive review by Lear et al, [18] suggested that the most appropriate method for small sediment volumes was the DNeasy PowerSoil kit (Qiagen, Germany), which was used in the current study.…”
Section: Introductionmentioning
confidence: 98%